Immediate Effects of (Simulated) Age-Related Hearing Loss on Cognitive Processing and Performance for the Backward-Digit-Span Task - Füllgrabe, Christian; Öztürk, Ozan Cem (Frontiers in Aging Neuroscience, 2022)
The recall of auditorily presented sequences of digits in reverse order (also known as the Backward Digit Span, BDS) reflects a person’s information storage and processing abilities which have been used to predict in speech-in-noise intelligibility. However, especially in clinical and experimental audiology, persons who are administered the BDS task are often affected by hearing loss (HL). If uncorrected, HL can have immediate assessment-format-related effects on cognitive-test performance as well as result in long-term neuroplastic changes impacting on cognitive functioning. In the present study, an impairment-simulation approach, mimicking mild-to-moderate age-related HLs typical for persons aged 65, 75, and 85 years, was used in 19 young normal-hearing participants to evaluate the impact of HL on cognitive performance and the cognitive processes probed by the BDS task. Participants completed an auditory version of the BDS task in several listening conditions, as well as several established visual tests of short-term and working memory. The results indicated that BDS performance was impaired by simulated HL representing persons aged 75 years and above. In the normal-hearing condition, BDS performance correlated significantly with performances on tests of both short-term and working memory. In the most severe simulated HL condition, BDS performance only correlated with performance on the working-memory tests. In summary, simulated (and, by extrapolation, actual) age-related HL negatively affects cognitive-test performance, and may change the composition of the cognitive processes contributing to the completion of a cognitive task.